2014
DOI: 10.1182/blood-2014-04-566737
|View full text |Cite
|
Sign up to set email alerts
|

Activity of SL-401, a targeted therapy directed to interleukin-3 receptor, in blastic plasmacytoid dendritic cell neoplasm patients

Abstract: • SL-401 was well tolerated, and a single course of treatment produced a high rate of objective responses in BPDCN patients.This is the first prospective study of treatment of patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN), an aggressive hematologic malignancy derived from plasmacytoid dendritic cells that typically involves the skin and rapidly progresses to a leukemia phase. Despite being initially responsive to intensive combination chemotherapy, most patients relapse and succumb to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 48 publications
1
162
0
2
Order By: Relevance
“…These data showed that a single cycle of SL-401 induced major responses in 78% of the patients. 24 The way to use SL-401 in BPDCN patients must, howe ver, be discussed in the light of data from literature obtained in such patients. SL-401 can be used to consolidate the effects of first-line chemotherapy, reducing the number of relapses, which always occur after chemothe rapy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that a single cycle of SL-401 induced major responses in 78% of the patients. 24 The way to use SL-401 in BPDCN patients must, howe ver, be discussed in the light of data from literature obtained in such patients. SL-401 can be used to consolidate the effects of first-line chemotherapy, reducing the number of relapses, which always occur after chemothe rapy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of the disease, prospective clinical trials to define the role of autologous and allogeneic HCT in BPDCN may not be feasible. A better understanding of the pathophysiology and novel therapeutic agents for BPDCN are urgently needed [15].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include unconjugated monoclonal antibodies, T-cell engaging bispecific antibodies, immunotoxins, and chimeric antigen receptor (CAR)-modified T cells (36)(37)(38)(39)(40)(41). Although each of the modality has its own advantages, our study shows that SGN-CD123A is highly active against AML models regardless of cytogenetic profiles and MDR status, and can be effectively combined with quizartinib.…”
Section: Mdr Proteins (30mentioning
confidence: 94%